ADP-ribosylhydrolase 3 (ARH3), Not Poly(ADP-ribose) Glycohydrolase (PARG) Isoforms, Is Responsible for Degradation of Mitochondrial Matrix-associated Poly(ADP-ribose) - Niere, Marc (American Society for Biochemistry and Molecular Biology, 2012)
Important cellular processes are regulated by poly(ADP-ribosyl)ation. This protein modification is catalyzed mainly by nuclear poly(ADP-ribose) polymerase (PARP) 1 in response to DNA damage. Cytosolic PARP isoforms have been described, whereas the presence of poly(ADP-ribose) (PAR) metabolism in mitochondria is controversial. PAR is degraded by poly(ADP-ribose) glycohydrolase (PARG). Recently, ADP-ribosylhydrolase 3 (ARH3) was also shown to catalyze PAR-degradation in vitro. PARG is encoded by a single, essential gene. One nuclear and three cytosolic isoforms result from alternative splicing. The presence and origin of a mitochondrial PARG is still unresolved. We establish here the genetic background of a human mitochondrial PARG isoform and investigate the molecular basis for mitochondrial poly(ADP-ribose) degradation. In common with a cytosolic 60-kDa human PARG isoform, the mitochondrial protein did not catalyze PAR degradation because of the absence of exon 5-encoded residues. In mice, we identified a transcript encoding an inactive cytosolic 52-kDa PARG lacking the mitochondrial targeting sequence and a substantial portion of exon 5. Thus, mammalian PARG genes encode isoforms that do not catalyze PAR degradation. On the other hand, embryonic fibroblasts from ARH3(−/−) mice lack most of the mitochondrial PAR degrading activity detected in wild-type cells, demonstrating a potential involvement of ARH3 in PAR metabolism.